Special issue «Environment change on the Mongolian plateau: atmosphere, forests, soils and water» - Daniel Karthe; Sergey Chalov; Alexander Gradel; Antonín Kusbach (Geography, Environment, Sustainability, 2019)
The Mongolian Plateau forms a part of the Central Asian Plateau and covers an area of approximately 3,200,000 square kilometers in Mongolia and adjacent areas in China and Southern Siberia. It contains one of the world’s largest grassland areas, with the Gobi desert in the south and a transition via steppe and forest steppe to the taiga and mountain tundra in the North (Dulamsuren et al. 2005; Miao et al. 2015). Due to its location, the Plateau's climate is continental and semi-arid to arid, characterized by low precipitation (about 250 mm on average), high potential evapotranspiration (almost 1000 mm on average), large temperature amplitudes, long and harsh winters and recurrent droughts (Dorjgotov 2009; Liu et al. 2019). The Mongolian Plateau mostly drains into the Arctic Ocean basin, including the system of the Selenga River and Lake Baikal, which is not only the world's largest freshwater lake but also a natural heritage of global importance (Kasimov et al. 2017). Hydrologically, parts of the plateau also belong to the Pacific Ocean and Central Asian internal drainage basins.